(untitled) (Jurnal Riset Mahasiswa, 2023)
This research approach is a qualitative approach. The subjects in this study were 1 Head of the Protocol Subdivision, 1 Head of the Leadership Communications Subdivision and 1 staff of the Temanggung Regency Secretariat. While the object of research is the effectiveness of the communication pattern of the protocol section in supporting the tasks of regional leaders in Temanggung Regency, then data analysis uses an interactive model as proposed by Miles, M. B. and Huberman. The result is that the communication pattern is executed with the wheel pattern, chain pattern, Y pattern, and circle pattern. The obstacles faced by the Protocol Section of the Temanggung Regency Secretariat in supporting the tasks of the Temanggung Regency Regional Leader, the Head of the Protocol and Communications Division Leader is the lack of coordination between protocols with the Regent or with the related OPD regarding activities and publication of OPD programs, there are still gaps between the Sections Protocol and Communication of Leaders and leaders (Regent), causing late information that should be delivered at the right time, lack of competence of the Protocol Section employees who control IT for website management, social media (facebook, Instagram, Twitter, etc.) and SMS gateway, the lack of employees in the Protocol and Communications Division of the Leaders compared to the many tasks carried out in facilitating the activities of regional leaders (Regents). Efforts to improve communication of the Protocol and Communications Section of the Regional Secretariat of Temanggung Regency in supporting the tasks of the Temanggung Regency Regional Leadership, are increasing coordination between protocols with the Regent or with related OPD regarding activities and publications of OPD programs, increasing communication media between the Protocol and Communication Section of Leaders and leaders. (Regent), increasing the competence of the Protocol Division employees in the IT sector as well as completing the facilities and infrastructure, optimizing the performance of the Protocol and Communications Division employees and proposing additional employees for the Protocol and Leadership Communications Division.